Expression and permeation properties of the K(+) channel Kir7.1 in the retinal pigment epithelium - Shimura, Masahiko (Blackwell Science Inc, 2001)
1. Bovine Kir7.1 clones were obtained from a retinal pigment epithelium (RPE)-subtracted cDNA library. Human RPE cDNA library screening resulted in clones encoding full-length human Kir7.1. 2. Northern blot analysis indicated that bovine Kir7.1 is highly expressed in the RPE. 3. Human Kir7.1 channels were expressed in Xenopus oocytes and studied using the two-electrode voltage-clamp technique. 4. The macroscopic Kir7.1 conductance exhibited mild inward rectification and an inverse dependence on extracellular K(+) concentration ([K(+)](o)). The selectivity sequence based on permeability ratios was K(+) (1.0) ≈ Rb(+) (0.89) > Cs(+) (0.013) > Na(+) (0.003) ≈ Li(+) (0.001) and the sequence based on conductance ratios was Rb(+) (9.5) >> K(+) (1.0) > Na(+) (0.458) > Cs(+) (0.331) > Li(+) (0.139). 5. Non-stationary noise analysis of Rb(+) currents in cell-attached patches yielded a unitary conductance for Kir7.1 of ≈2 pS. 6. In whole-cell recordings from freshly isolated bovine RPE cells, the predominant current was a mild inwardly rectifying K(+) current that exhibited an inverse dependence of conductance on [K(+)](o). The selectivity sequence based on permeability ratios was K(+) (1.0) ≈ Rb(+) (0.89) > Cs(+) (0.021) > Na(+) (0.003) ≈ Li(+) (0.002) and the sequence based on conductance ratios was Rb(+) (8.9) >> K(+) (1.0) > Na(+) (0.59) > Cs(+) (0.23) > Li(+) (0.08). 7. In cell-attached recordings with Rb(+) in the pipette, inwardly rectifying currents were observed in nine of 12 patches of RPE apical membrane but in only one of 13 basolateral membrane patches. 8. Non-stationary noise analysis of Rb(+) currents in cell-attached apical membrane patches yielded a unitary conductance for RPE Kir of ≈2 pS. 9. On the basis of this molecular and electrophysiological evidence, we conclude that Kir7.1 channel subunits comprise the K(+) conductance of the RPE apical membrane.